Analysis of a immunity system using qualitative methods - Kavaliauskas, Algis (Lietuvos matematikos rinkinys, 2002)
The article deals with analysis of reciprocity model of cancer cells and lymphocites, when cancer cells are restricted by cylindrical surfaces. The growth of cells is possible in the direction of radius and altitude in different speeds. The qualitative analysis of stationary values of this model is done.